Front Cover: Protonation of p‐Benzoquinone in Superacidic Solutions (Z. Anorg. Allg. Chem. 23/2018). Issue 23 (5th December 2018) - Schickinger, Manuel; Siegert, Markus; Morgenstern, Yvonne; Zischka, Florian; Stierstorfer, Karin; Kornath, Andreas
Abstract : The Front Cover shows the solid state structure of protonated p‐benzoquinone salt. Obviously, the cations prefer to share protons instead of being isolated. The protonation was achieved in the superacidic systems HF/AsF5 and HF/SbF5, representing the first example of salts containing a protonated p‐benzoquinone moiety. The experimental results are discussed together with quantum chemical calculations in the article by Manuel Schickinger, Markus Siegert, Yvonne Morgenstern, Florian Zischka, Karin Stierstorfer, and Andreas Kornath on page1564 ff .